The distributed author and the poetics of complexity: a comparative study of the sagas of Icelanders and Serbian epic poetry - Ranković, Slavica (2006)
The thesis brings together Íslendingasögur and srpske junačke pesme, two historically and culturally unrelated heroic literatures, literatures that had, nevertheless, converged upon a similar kind of realism. This feature in which they diverge from the earlier European epics - Beowulf, Nibelungenlied, La Chanson de Roland, is the focal point of this study. Rather than examining it solely in terms of verisimilitude and historicism with which it is commonly associated, I am approaching it as an emergent feature (emergent realism) of the non-linear, evolutionary dynamics of their production (i.e. their networked, negotiated authorship), the dynamics I call the distributed author.